Effect of the Wick and the Working Medium on the Thermal Resistance of FPHP - Sun, Bin; Peng, Cheng; Yang, Di; Li, Hongwei (Frontiers in Energy Research, 2018)
This paper introduces a novel micro-deep, triangle-grooved wick, and compares the performance of the flat plate heat pipe (FPHP) with various types of wicks, including foam metal copper wick, sintered copper powder wick, copper mesh wick, micro-deep rectangle-grooved wick, and micro-deep triangle-grooved wick. Test results verified the feasibility of the nanofluids applied to FPHP. Tested working fluids included deionized water, Cu-water nanofluids, carbon-coated copper nanofluids and multi-walled carbon nanotube (MWCNT) nanofluids. These nanofluids were applied on foam metal FPHP and the results were compared. The results indicated that the metal foam wick is better than the other heat pipe wicks, in the contrast experiment, when the heating power is 100 w, the thermal resistance is 0.1238°C/K. The thermal resistance of micro-deep triangle-grooved wick FPHP is 15% lower than the micro-deep rectangle-grooved wick FPHP; The optimal filled ratio of 40% can make flat heat pipe have good performance; With the increase of mass fraction of nanofluid, the thermal resistance decreased first and then increased, the best mass fraction is 0.5%, the thermal conductivity of carbon-coated copper nanofluids FPHP is optimal, the average thermal resistance is 0.1369°C/K, and is 17 and 9% lower than the multi-walled carbon nanofluids and copper FPHP, and is 46% lower than the deionized water FPHP; The gravitational stability of the heat pipe is verified by the experiments.